Synthesis and biological evaluation of new “gramine” opened derivatives of vinorelbine - Anh, Ngo Quoc (Vietnam Journal of Chemistry, 2015)
New “gramine” opened derivatives was synthesized from an ammonium salt of vinorelbine or simplified analogues. Their structures were elucidated by NMR, MS or compared with the known similar analogues. Compound 8 exhibits a good cytotoxicity on the KB cell line as well as a good inhibiting activity toward the polymerisation of tubulin.